Studying the Effect of Shrinkage on the Bond Strength of Mortars, Applied to Substrate Concrete, Using “Friction-Transfer” and “Pull-Off” Methods - Mahmood Naderi (Iranian Society of Structrual Engineering (ISSE), 2021)
Considering the differences that exist between the laboratory and site conditions, the in-situ estimation of bond strength of repair mortars is important. Therefore, in this paper, the results obtained from the use of two methods, “Friction-transfer” and “Pull-off”, for measuring the shear and tensile bond strength of repair mortars applied to substrate concrete, are presented. Since the drying shrinkage of the repair mortar has considerable effect on their adhesion, the shrinkage of the mortars is considered. In order to increase the accuracy of the measured bond strength of the repair mortars, substrate concrete with saw cut surface was employed to minimize the interferences occurring between the pure adhesion and the mechanical keying effects of the rough surfaces. The age of the substrate concrete at the time of the application of repair mortar was 90 days and after curing under different conditions, the repair/concrete bond strength was measured at different ages. For measuring the shrinkages of the repair mortars, nine standard shrinkage samples were prepared and their shrinkages were measured. Regarding the effect of the curing process on the drying shrinkage of the repair mortars, two different curing systems of “covering with wet hessian and polythene sheet” and “stored in the laboratory”, for 7 and 90 days were considered. The results tend to show that, the amount of the aggregates and the associated cement paste have substantial effects the shrinkage of the repair mortars. It was also seen that the shrinkage causes reduction on the shear and tensile bond strength at the repair/concrete interface. Furthermore, the reduction of the shear bond strength seemed to be slightly more than the corresponding reduction of the tensile bond strength. A very high correlation was also observed between the related shear and tensile bond strength of the repair mortars.